Application of Situational Virtual Reality System to improve Learning Performance of Traditional Hair Cutting Skills - hsu, chu huang; Sheng-Min Hsien; Rong-Chi Chang (Advances in Social Sciences Research Journal, 2019)
The study mainly relates to design and develop a system of “Hair Cutting and Blowing skills training” to assist hairdressing skills learning by theming on two major items of “hair cutting and blowing” skills” in the "Women’s Hairdressing Certification C" test. The study has set 40 students who major in Fashion Modeling Department in northern Taiwan as experimental samples, wherein 20 students of experimental group were trained in the virtual reality hairdressing and hygiene skills training system; and 20 students of the control group were trained in traditional teaching methods. The result of the study has found that the experimental group’s learning performance in the comprehensive skills is better than the control group, and the growth rate also reached a significant level. Through the test of the technology acceptance model, this “Hair Cutting and Blowing skills training” system can assist in the learning of skills and enhance students’ motivation in learning. From unfamiliar skill training to proficiency, through the repeated practice in the virtual reality simulation environment, it helps in increasing hand feeling and confidence which can also help to reduce the amount of exercise materials needed for hair and blowing skills training.